Pemberdayaan Masyarakat Dusun Upunyor Melalui Program Kuliah Kerja Nyata - Sigit Sugiarto; Ratnah Kurniati MA; Asmirani Alam; Dian Rubiana Suherman; Edy Sony; Sitti Fatimah Kamaruddin; Lestari Lestari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The implementation of the Real Work Lecture (KKN) program for PSDKU students at Pattimura University aims to improve the creative economy of village communities and help village communities solve existing problems, including in Upunyor Hamlet. In achieving the objectives of implementing KKN, Upunyor Hamlet KKN students carry out various work programs in the form of priority programs, superior programs, and companion programs. The work program implemented was an initiative of Upunyo Hamlet KKN students and a proposal from hamlet residents through the Head of Upunyor Hamlet. Based on the results of the community satisfaction index questionnaire, in general the community feels very satisfied with the work program that has been implemented by the Upunyor Hamlet KKN students. So it can be concluded that Upunyor Hamlet KKN students can improve the creative economy of the Upunyor Hamlet community and help the community in solving existing problems.